Scientific thinking in speech and language therapy - Lum, Carmel (L. Erlbaum Associates, Publishers, 2002)
An introduction to the history and philosophy of science, scientific methods, and fundamental concepts underlying scientific thinking and reasoning. It provides many illustrative examples from speech and language pathology to help students and practitioners contextualise these ideas.